The Garda Inspectorate: Driving Collaborative Reform Through a Model of Equilibrated Governance - O'TOOLE, KATHLEEN (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
In the Garda Síochána Act of 2005, the Irish Government established a new oversight body, the Garda Inspectorate, to drive reform in its national police service, An Garda Síochána. Appointed in 2006 as the first Chief Inspector of this nascent body, I was tasked to build the Inspectorate as an entity and to embed in its operations a system for driving effective and sustainable change. Determined to bring rigour and a scholarly approach to the Inspectorate’s work, I applied insider action research methodology. Over a five-year period, the Inspectorate undertook five core projects in alignment with this approach. Each of these projects produced practical and achievable recommendations for reform and innovation in Irish policing. Collectively, these projects formed the meta-cycle of my thesis work. In the course of the meta-cycle, I identified the recurring organisational themes of agile leadership, authentic engagement, and contextual intelligence that culminated in a model for driving collaborative reform that I term ‘equilibrated governance.’ Understanding ‘governance’ in this context, consistent with cited literature, as those psychological constructs and practises that build commitment and trust, I discuss how this model of equilibrated governance proved effective in driving reforms in the Garda Síochána, and also suggest it may serve as an effective governance framework in other disciplines.
APPROVED
Keywords: Equilibrated Governance